Aortic VCAM‐1: an early marker of vascular inflammation in collagen‐induced arthritis. Issue 5 (9th February 2016) - Denys, Anne; Clavel, Gaëlle; Lemeiter, Delphine; Schischmanoff, Olivier; Boissier, Marie‐Christophe; Semerano, Luca
Abstract: Cardiovascular disease (CVD) is a major cause of morbidity and mortality in rheumatoid arthritis (RA). There are limited experimental data on vascular involvement in arthritis models. To study the link between CVD and inflammation in RA, we developed a model of vascular dysfunction and articular inflammation by collagen‐induced arthritis (CIA) in C57Bl/6 (B6) mice. We studied the expression of vascular inflammatory markers in CIA with and without concomitant hyperlipidic diet (HD). Collagen‐induced arthritis was induced with intradermal injection of chicken type‐II collagen followed by a boost 21 days later. Mice with and without CIA were fed a standard diet or an HD for 12 weeks starting from the day of the boost. Arthritis severity was evaluated with a validated clinical score. Aortic mRNA levels of vascular cell adhesion molecule‐1 (VCAM‐1), inducible nitric oxide synthase (iNOS) and interleukin‐17 were analysed by quantitative RT‐PCR. Vascular cell adhesion molecule‐1 localization in the aortic sinus was determined by immunohistochemistry. Atherosclerotic plaque presence was assessed in aortas. Collagen‐induced arthritis was associated with increased expression of VCAM‐1, independent of diet. VCAM‐1 overexpression was detectable as early as 4 weeks after collagen immunization and persisted after 15 weeks. The HD induced atheroma plaque formation and aortic iNOS expression regardless of CIA. Concomitant CIA and HD had no additive effect on atheroma or VCAM‐1 or iNOS expression. CIA and an HD diet induced a distinct and independent expression of large‐vessel inflammation markers in B6 mice. This model may be relevant for the study of CVD in RA.